Funcionalidad y demencia - Fuentes G. , Patricio (Revista Hospital Clínico Universidad de Chile, 2008)
The functionality, that ability permits the people to be able to face the basic and complex needs of the daily life, invariably will be affected in the dementias. This progressive functional limitation acquires importance because affects the quality of life of patients and caregivers and even increases the risk of mortality of the patient with dementia. The measurement of the function, with different neuropsychological tools, is an essential part of the clinical practice and it has been constituted in one of the main objectives in the follow up and in the evaluation of interventions in dementia. Cognitive training programs and antidementia drugs, like cholinesterase inhibitors or memantine, have shown modest but statistically significant benefits in some activities of daily living.